Learning from Manoomin: Restor(y)ing relationships between Anishinaabeg, settlers, and more-than-human beings in the Great Lakes Basin - Paridy, Caitlin Jakusz (University of Waterloo, 2021)
Positioned between multiple worlds, Manoomin - wild rice is described within the Mishomis Book by the leader and activist Edward Benton Benai, as one of the sacred gifts from the Earth to the Anishinaabeg of the Great Lakes Basin. Over the past few centuries however, this relationship has been impacted by settler colonial land practices such as logging, mining, the creation of waterways and removal of harvesting rights through official documents and land dispossessions. While these movements of settler colonialism from governments and individuals have fragmented the relationship between Manoomin and the Anishinaabeg, there has been a growing movement by Indigenous and non-Indigenous individuals and communities to restore wild rice in this region through reseeding, and wetland restoration efforts. Working to directly challenge Western ways of knowing through the study of Indigenous methodologies and reconciliation research from authors such as Leanne Betasamosake Simpson, Shawn Wilson, Ruth Koleszar-Green, and Deborah McGregor, this thesis asks how the restoration of Manoomin might provide a framework to understand relationships between Indigenous peoples, settlers, and more-than-human beings. Three initiatives restoring Manoomin in the Great Lakes Basin are explored with drawings, reflections, and conversation, which in turn document the evolution of the land through the “restorying” of relationships, following principles such as Vanessa Watt’s “Place-Thought” and Willie Ermine’s “Ethical Space”. Within each of the three initiatives, Manoomin offers a range of lessons; beginning with sovereignty, harvesting rights, and contrasting perceptions of land within the restoration of wild rice in Pigeon Lake, ‘Ontario’. The dynamics of co-management are revealed through the restoration of the so-called St. Louis River in ‘Duluth, Minnesota’, one of the most polluted watersheds in the region and the sixth stop along the Anishinaabeg migration from the East coast of Turtle Island. Finally, the importance of establishing ...